THE IMPACT OF PEER ASSESSMENT ON STUDENTS’ RECOUNT TEXT - Nur Laili Indasari; Oikurema Purwati; Syafiul Anam (Universitas Islam Negeri Alauddin Makassar, 2019)
Peer Assessment is one of the alternative methods to enhance the students’ motivation and ability in writing. Providing feedback is the goal of peer assessment. It is not an easy task as it is required an ability to deliver the feedback critically and competence to master the knowledge of writing. Therefore, the present study is going to explore the impact of giving feedback in the peer assessment process on students’ recount text and to acknowledge the students’ challenges while giving and receiving feedback in that process. Qualitative study assisted the researcher to get the data. The university students in the second semester became the subjects of the study. Documents and interviews were techniques to collect the data. The results revealed that the students’ first draft and the last draft of recount text got improvements mainly on the aspect of grammar. Meanwhile, most students’ challenges while giving and receiving feedback in the process of peer assessment were the aspect of psychology and the knowledge of grammar. In conclusion, the process of peer assessment which involves giving and receiving feedback provides a positive impact on the students’ recount text and the challenges which are faced by the students can be used as inputs for the lecturer in teaching.